2014
DOI: 10.1186/1742-6405-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Virologic outcomes of second-line antiretroviral therapy in Eastern European country of Georgia

Abstract: BackgroundData on the effectiveness of second-line antiretroviral therapy (ART) in resource-limited countries of Eastern Europe is limited. Objective of this study was to evaluate virological outcomes of second-line ART in Georgia.MethodsWe conducted retrospective analysis using routinely available program data. Study included adult HIV-infected patients with confirmed HIV drug resistance, who were switched to second-line ART from August 2005 to December 2010. Patients were followed until July 1, 2011. Primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
(15 reference statements)
0
12
1
1
Order By: Relevance
“…Cette étude s'est fixée pour objectifs de déterminer la prévalence de la NO des PVVIH sous antirétroviraux, de déterminer les caractéristiques socio-démographiques et les facteurs de la NO. Ces objectifs sont proches de ceux de Chkhartishvil et al qui s’étaient penchés sur l’évaluation de l'adhérence aux TAR dans les pays de l'Europe de l'Est [ 20 ].…”
Section: Discussionunclassified
“…Cette étude s'est fixée pour objectifs de déterminer la prévalence de la NO des PVVIH sous antirétroviraux, de déterminer les caractéristiques socio-démographiques et les facteurs de la NO. Ces objectifs sont proches de ceux de Chkhartishvil et al qui s’étaient penchés sur l’évaluation de l'adhérence aux TAR dans les pays de l'Europe de l'Est [ 20 ].…”
Section: Discussionunclassified
“…The total number of days from enrolment was determined as follows: until study staff deactivated the device (definition 1), until the last event recorded (definition 2), or until the repeat viral load date (definition 3). We considered two cut-offs to define good adherence; either taking at least 80 % (missing ≥20 %) or taking at least 95 % (missing ≥5 %) of the prescribed medication [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Continuous variables are described using medians with corresponding interquartile ranges (IQR) and categorical variables are expressed as simple proportions. For the intervention cohort log-binomial regression was used to estimate the association between poor adherence (defined as either ≤ 95 % or ≤ 80 % [ 7 ] of required scheduled dose) and unsuppressed virus (≥400 copies/ml) between 3 and 6 months after enrolment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO treatment guidelines recommended combination antiretroviral therapy (cART) initiation to all HIV infected adolescents to prevent HIV-related morbidity and mortality [7]. Some evidence has shown that access to cART to treat HIV infection and AIDS in resource-poor countries had improved over the past several years [8]. The cART when taken correctly could lead to sustained viral suppression and reduction in occurrence of AIDS-defining and non-AIDS-defining complications.…”
Section: Introductionmentioning
confidence: 99%